Teamwork between registered nurses and unlicensed assistive personnel in acute care settings: A scoping review - Kang Lynn Wong; Wei Ling Chua; Peter Griffiths; Qin Ling Pearlyn Goh; Kye Wern Chelsea Low; Jia Qi Apphia Tan; Sok Ying Liaw (International Journal of Nursing Studies Advances)
Background: Unlicensed assistive personnel are increasingly employed to support the nursing workforce in providing bedside care. Aim: To scope the literature on the factors influencing teamwork between registered nurses and unlicensed assistive personnel in acute care settings Methods: A scoping review was conducted using the Arksey and O'Malley (2005) framework. Eight electronic databases were searched from inception of each database to August 2024 to locate studies that reported issues relating to teamwork between registered nurses and unlicensed assistive personnel on patient care in general wards of acute care settings. Two reviewers independently screened titles, abstracts, and full text for eligibility. The data were extracted, analysed, and synthesised using the data-based convergent qualitative synthesis Results: Thirty-eight studies were included. Five themes were generated: (1) role clarity, (2) delegation, (3) communication, (4) ward culture and practice, and (5) interpersonal relationships. Challenges in registered nurses–unlicensed assistive teamwork include unclear roles and responsibilities, ineffective delegation, and communication barriers. Work culture that excludes unlicensed assistive personnel from shift handovers were found to hinder shared goals for patient care. The importance of interpersonal relationships between registered nurses and unlicensed assistive personnel was highlighted to aid in the power disparity between them. Conclusions: This review found suboptimal teamwork between registered nurses and unlicensed assistive personnel. Teamwork between registered nurses and unlicensed assistive personnel can be improved through clearly defined roles and responsibilities, better delegation practices, effective communication, and improved interpersonal relationships. Future research should focus on optimising communication processes and enhancing registered nurses’ delegation skills through education.